(untitled) (e-Journal of Linguistics, 2026)
This study aims to describe the forms of omission regarding the prefix meng- and the suffix –kan in Indonesian poetry and to explain the resulting stylistic functions. This study employs a qualitative method with a linguistic stylistic approach at the morphological level. Data consisting of Indonesian poems containing affix omissions were collected through a literature review technique and analyzed by identifying, classifying, and interpreting the forms of omission. The results indicate that the omission of the prefix meng- and the suffix –kan is a form of linguistic deviation that is systematic and deliberately employed by poets. This omission not only simplifies word forms but also serves to create aesthetic effects, strengthen rhythm, and deliver a more expressive and communicative linguistic impression. Significantly, these findings confirm that morphological deviation in poetry is a stylistic strategy reflecting the poet’s creativity and distinctive style. The implications of this study highlight the importance of stylistic analysis in understanding the relationship between linguistic structure and aesthetic value in literary works, particularly in Indonesian poetry